Point prevalence survey of antibiotic use in Mexican secondary care hospitals. - Federico A Zumaya-Estrada; Celia M Alpuche-Aranda; Hilda Ivonne Huerta Icelo; Felipe D Neri-Estrada; Verónica M Calixto Silva; Haydee E Quiroz Escoriza; Jesus Ulises Garza-Ramos; Pedro J Saturno-Hernandez (PLoS ONE)
Introduction Tackling the inertia of growing threat of antimicrobial resistance (AMR) requires changes in how antibiotics are prescribed and utilized. The monitoring of antimicrobial prescribing in hospitals is a critical component in optimizing antibiotic use. Point prevalence surveys (PPSs) enable the surveillance of antibiotic prescribing at the patient level in small hospitals that lack the resources to establish antimicrobial stewardship programs (ASP). In this study, we analyzed antibiotic use at two public secondary care hospitals in Mexico using PPSs. Methods Following WHO methodology, we conducted four cross-sectional PPSs on antibiotic use in two public secondary care facilities in Mexico: two surveys in a women's specialty hospital (H1) and two in a general referral hospital (H2). We collected data from clinical records of all patients with active antibiotic prescriptions (APs) across the medical, surgical, and mixed (MIX) wards, and intensive care units (ICUs). Descriptive statistics were computed to analyze the PPSs data using Stata. Results The PPSs collected data on 127 patients, and 283 active APs. The prevalence of antibiotic use was 60.4% (H1, n = 29/48) and 70.5% (H2, n = 98/139). Antibiotics were more frequently used among patients in the MIX wards (H1: 87.5%, n = 14/16) and ICUs (H2: 90%, n = 9/10). The most frequent patient indications for antibiotic use were medical prophylaxis (H1: 51.7%, n = 15/29), community-acquired infections (H2: 42.9%, n = 42/98), and preoperative prophylaxis (H1: 27.6%, n = 8/29; H2: 23.5%, n = 23/98). The APs were mostly empirical (H1: 97%, n = 64/66; H2: 98.2%, n = 213/217), and parenterally administered (H1: 90.9%, n = 60/66; H2: 96.8%, n = 210/217). Most clinical records lacked documented post-prescription reviews (H1: 82.8%, n = 24/29; H2: 98%, n = 96/98). Preoperative prophylaxis was predominantly administered as multiple doses for more than one day. Penicillins with extended-spectrum (24.2%, n = 16/66), aminoglycosides (22.7%, n = 15/66), and first-generation cephalosporins (16.7%, n = 11/66) were the most prescribed antibiotic classes in H1, while third-generation cephalosporins (35%, n = 76/217), fluoroquinolones (14.3%, n = 31/217), and carbapenems (13.4%, n = 29/217) were the most prescribed in H2. No hospital had formally established ASP. Conclusions This study shows high prevalence rates of antibiotic use and variations in commonly prescribed antibiotic classes in public Mexican secondary care hospitals, along with shared practices in broad-spectrum antibiotic prescription. PPS-based surveillance enables the identification of specific targets to optimize antibiotic use according to the healthcare needs of patients in each hospital and facilitates comparative evaluations across hospitals.